Hemangiopericytoma arising from the cartilage of the external auditory canal. Issue 5 (23rd January 2016) - Castiglione, Melina; Nardo, Luciano; Ottaviani, Francesco
ABSTRACT: Background: Hemangiopericytomas (HPCs) are soft tissue tumors with histological variability and unpredictable clinical and biological behavior. HPCs in the head and neck are uncommon, the growth pattern is nonspecific; thus, diagnosis is often made by exclusion. Methods: A 43‐year‐old man complained of a short history of right ear pain associated with a growing mass in the right external auditory canal. Subsequent hearing loss in the right ear brought the patient to undergo a CT scan and an MRI. The relevant literature was also reviewed. Results: The imaging revealed a neoplasm arising from the floor of the right external auditory canal. The neoplasm was removed with the diagnosis of HPC. Conclusion: The literature reports few cases of HPC of the external auditory canal. Their rarity in this area leads to difficulties in diagnosis. Morphology is not predictive of their behavior, so close follow‐up is mandatory for their correct management. © 2015 Wiley Periodicals, Inc. Head Neck 38: E108–E110, 2016